MENENTUKAN FORMULA CADANGAN PREMI ASURANSI JIWA LAST SURVIVOR MENGGUNAKAN METODE NEW JERSEY - DWIPAYANA, I GUSTI AGUNG GEDE; WIDANA, I NYOMAN; SARI, KARTIKA (E-Jurnal Matematika; Vol 8 No 4 (2019), 2019)
Last survivor life insurance is a type of life insurance for two or more people, with premium payment up to the last death of the insured and at that time also provide the benefit from the insurer. The purpose of this research was to determine the formula for last survivor life insurance premium reserve using New Jersey method. To calculate the reserve: first we determine the benefit, and then the annuity and finnaly the annual premium. The premium reserve value in the New Jersey method on first year is zero. The premium reserve in the New Jersey method starts in the second year, for  years, with  where n represents the term of the insurance participant’s contract.